Latin America through the lens of social cohesion : selected indicators (UN ECLAC Santiago, 2010)
Provides the first regional overview on social cohesion, a descriptive and comparative background for examining the progress and current status in the countries of Latin America regarding the three pillars of social cohesion : social gaps, institutional operation and citizen support.
Keywords: SOCIAL INTEGRATION